2021
DOI: 10.7150/thno.50281
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating lncRNA Platr4 regulates NLRP3 inflammasome to ameliorate nonalcoholic steatohepatitis in mice

Abstract: Background: Understanding the molecular events and mechanisms underlying development and progression of nonalcoholic steatohepatitis is essential in an attempt to formulating a specific treatment. Here, we uncover Platr4 as an oscillating and NF-κB driven lncRNA that is critical to the pathological conditions in experimental steatohepatitis Methods: RNA-sequencing of liver samples was used to identify differentially expressed lncRNAs. RNA levels were analyzed by qPCR and FISH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…Several reports have revealed that NF-κB mediates the inflammatory response of tumour cells after exposure to NETs, and NETs can activate the NF-κB signalling pathway ( 42 , 54 , 66 ). Growing evidence suggests that NF-κB, a critical transcription factor, is an upstream regulator of NLRP3 and affects the expression of NLRP3 inflammasome components ( 32 , 67 69 ). Lin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have revealed that NF-κB mediates the inflammatory response of tumour cells after exposure to NETs, and NETs can activate the NF-κB signalling pathway ( 42 , 54 , 66 ). Growing evidence suggests that NF-κB, a critical transcription factor, is an upstream regulator of NLRP3 and affects the expression of NLRP3 inflammasome components ( 32 , 67 69 ). Lin et al.…”
Section: Discussionmentioning
confidence: 99%
“… 62 , 63 Lin et al reported that Nr1d1 can regulate lncRNA Platr4 , which inhibits NLRP3 transactivation by preventing the binding of NF-κB to κB sites. 64 In this study, exogenous expression of Hmga2 partially blocked the downregulated expression of cytokines by SR9009 treatment in BV2 cells. Western blot analysis revealed that Hmga2 overexpression alleviated the inhibitory effects of p-p65 and p-IKK by SR9009 treatment.…”
Section: Discussionmentioning
confidence: 53%
“…These PRRs recognize different PAMPs and DAMPs. Among them, NLRP3 is most frequently investigated and has the most diverse activators 3 , 6 , 30 , 40 , 41 . Unlike other PRRs, NLRP3 and pyrin can be activated without a direct contact with their activators.…”
Section: Inflammasome Complex Formation and Activationmentioning
confidence: 99%